Determinants of Midwife Performance in Lactation Management in Surakarta and Karanganyar, Central Java - Nurul Wahidah; Endang Sutisna Sulaeman; Uki Retno Setia Budihastuti (Masters Program in Public Health, Sebelas Maret University, 2018)
Background: Exclusive breastfeeding has been recommended by World Health Organization for reduction of infant illness and death. Midwives have an important role in lactation management, which includes: (1) Teaching all lactating mothers on how to successfully breastfeed and sustain it up to 2 years or more; (2) Coming in contact with mothers and infants to promote, protect, and support breastfeeding. However, exclusive breastfeeding coverage was still low at 80% nationally, 76.7% in Surakarta, and 61.1% in Karanganyar in 2016, suggesting low midwife performance in lactation management. This study aimed to determine factors associated with midwife performance in lactating management in Surakarta and Karanganyar, Central Java.Subjects and Method: This was an analytic observational study with a cross-sectional design. The study was conducted in community health center in Surakarta and Karanganyar, Central Java, from April to June 2018. A sample of 200 midwives was selected by simple random sampling. The dependent variable was performance in lactation management. The independent variables were skill, motivation, experience, health facility, and work load. The data were collected by questionnaire and analyzed by a multilevel logistic regression.Results: Midwife performance in lactation management increased with better skill (b= 2.06; 95% CI= 0.48 to 3.65; p= 0.011), strong motivation (b= 1.15; 95% CI= -0.09 to 2.41; p= 0.070), work experience (b= 2.06, 95% CI= 0.69 to 3.44, p= 0.003), and available facility (b= 2.29, 95% CI= 0.89 to 3.68, p= 0.001). Performance decreased with higher workload (b= -1.47; 95% CI= -2.76 to -0.18, p=0.025). Community health center had a contextual effect on midwives performance with ICC= 34.8%.Conclusion: Midwife performance in lactation management increases with better skill, strong motivation, work experience, and available facility. Performance decreases with higher workload. Community health center has a contextual effect on midwives performance.Keywords: performance, lactation management, determinant, midwifeCorresp ondence:Nurul Wahidah. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami No. 36 A, 57126, Surakarta, Central Java. Email: wahidahnurul246@gmail.com.Journal of Health Policy and Management (2018), 3(1): 26-33https://doi.org/10.26911/thejhpm.2018.03.01.04